Deep eutectic solvents and natural deep eutectic solvents for extraction and purification of proteins from animal and botanical sources - a review - Kumoro, Andri Cahyo; Wardhani, Dyah Hesti; Kusworo, Tutuk Djoko; Djaeni, Mohamad; Ping, Tan Chin; Alhanif, Misbahudin (International Journal of Technology, 2024)
The rising global population has led to an escalating demand for affordable, high-quality proteins intended for human consumption. Different efforts have been made to develop efficient and greener solvents for protein production. Most proteins are produced from raw plant and animal parts, but the use of the residues in commercial-scale protein production is very scarce. Therefore, this research aims to collect an overview of deep eutectic solvents (DESs) and natural deep eutectic solvents (NADESs) for protein extraction and purification. In this context, solvent type and operating parameters should also be selected to modify DESs and NADESs physicochemical characteristics for the achievement of high protein yield with preserved functional properties. The results show that appropriate implementation of combined DESs and NADESs with advanced extraction and purification techniques can improve protein yield and prevent detrimental effects on the extracted protein and environment. The application of DESs and NADESs can increase the efficiency of protein extraction and recovery in various parts of plants and animals by 55.72% and 98.16%, respectively, with purity reaching 99.82%. This research also reviews safety, environmental impacts, and drawbacks as well as shows feasible future recommendations for commercial-scale protein production processes. NADESs are safer than petroleum-based solvents but have higher toxicity than DESs. Magnetic adsorbent and magnetic solid-phase extraction methods have been shown to reduce labor-intensive steps, resulting in shorter operating times and superior protein recovery while maintaining functional properties. Meanwhile, protein producers' knowledge and motivation to use DES and NADES are strengthened.